Enhancing Students’ Communicative Competence through Classroom Tasks in Hospitality Training - Khafidhta Qudsiana Nurul Arifah; Endang Fauziati; Yeny Prastiwi (International Journal of Educational Research Excellence (IJERE), 2025)
This study explores how classroom tasks enhance students’ communicative competence in English in a receptionist training program using Project-Based Learning (PJBL). By incorporating role-playing, simulations, and task-based interactions reflecting real-life scenarios such as guest greetings, check-ins, complaint handling, and local knowledge sharing, the program aims to develop four components of communicative competence: grammatical, sociolinguistic, discourse, and strategic. A qualitative case study approach was employed, with data collected through classroom observations, interviews, and document analysis and then analyzed thematically. The findings show that tailored classroom tasks improve students’ ability to use appropriate grammar and vocabulary, adjust communication to social contexts, organize coherent responses, and employ strategies to overcome communication barriers. This study highlights the critical role of classroom tasks in bridging the gap between theoretical learning and professional demands, offering practical insights for educators to design effective ESP curricula tailored to the hospitality sector